2009
DOI: 10.1128/aac.00856-08
|View full text |Cite
|
Sign up to set email alerts
|

Association between Antimicrobial Consumption and Resistance in Escherichia coli

Abstract: During a 9-year study period from 1997 through 2005, the association between antimicrobial resistance rates in Escherichia coli and outpatient antimicrobial consumption was investigated in 20 hospital districts in Finland. A total of 754,293 E. coli isolates, mainly from urine samples, were tested for antimicrobial resistance in 26 clinical microbiology laboratories. The following antimicrobials were studied: ampicillin, amoxicillin-clavulanate, cephalosporins, fluoroquinolones, trimethoprim, trimethoprim-sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 25 publications
(38 reference statements)
3
45
0
1
Order By: Relevance
“…However, possibility of prescriptions for ciprofloxacin given by doctors to be purchased from outside cannot be ruled out. A significant association has been reported between amoxicillin use and fluoroquinolone resistance [19]. The high utilisation of amoxicillin would have contributed to ciprofloxacin resistance observed in our study.…”
Section: Discussionmentioning
confidence: 46%
“…However, possibility of prescriptions for ciprofloxacin given by doctors to be purchased from outside cannot be ruled out. A significant association has been reported between amoxicillin use and fluoroquinolone resistance [19]. The high utilisation of amoxicillin would have contributed to ciprofloxacin resistance observed in our study.…”
Section: Discussionmentioning
confidence: 46%
“…Unlike the majority of published studies, there were few significant correlations between antimicrobial prescription and subsequent resistance or vice versa (2,7,10,13,18). Overall carbapenem prescription was correlated with significant but slight changes in imipenem resistance in Acinetobacter blood isolates within the same time period.…”
Section: Discussionmentioning
confidence: 47%
“…Gram-negative bacterial resistance is of particular importance as there is a dearth of novel antibiotics directed against these organisms (1), which are increasing in prevalence worldwide (8,12,15). Logically, an association should exist between antibiotic consumption and Gram-negative bacterial resistance, and this was demonstrated in multiple studies in both the hospital and community settings (2,7,10,13,18). Causal relationships have been difficult to establish, however, and there are studies that have failed to show any interdependence (1,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, only a few associations were found between antimicrobial consumption and its resistance. Including the association between consumption of fluoroquinolone and its resistance, the majority of the associations studied were not significant [25]. Most of the research discussed above showed a linear relationship between the rate of antimicrobial use and drug resistance.…”
Section: Antimicrobial Consumptionmentioning
confidence: 92%